The acceptability and effectiveness of eHealth interventions to support assessment and decision-making for people with dementia living in care homes: A systematic review - Tunnard, India; Gillam, Juliet; Harvey, Catherine; Davies, Nathan; Vickerstaff, Victoria; Ellis-Smith, Clare; Evans, Catherine J. (Frontiers in Dementia, 2022)
Introduction As dementia progresses, care needs increase leading many to require 24-h care in care homes. eHealth interventions have the potential to improve care processes of assessment and decision-making for people with dementia. However, little is known on the acceptability and effectiveness in care homes. Aim To identify and explore the components, acceptability and effectiveness of eHealth interventions for people with dementia, families and staff to support assessment and decision-making in care homes. Methods A mixed methods systematic review using narrative synthesis. Four databases were searched (Embase, PsycINFO, MEDLINE, and CINAHL) from 2000 to July 2021. Quality appraisal used validated assessment tools appropriate for the study design. Results Twenty-six studies met eligibility criteria. Study designs and interventions were heterogeneous. Overall quality was high to moderate. Interventions that promoted supportive, practical learning through integrated working and provided staff with language to communicate resident symptoms were favored by staff. We found evidence that indicated residents were willing to use video consultations; however, families preferred face-to-face consultations. Fifteen studies considered effectiveness. Use of eHealth interventions indicates an improvement in resident outcomes in appropriate prescribing and advance care planning. Staff knowledge, confidence, and wellbeing were also improved. Hospitalisations were reduced when a video consultation component was implemented. Discussion Care home staff require support to meet the often multiple and changing care needs of residents with dementia. eHealth interventions can improve outcomes for staff and residents and facilitate integrated working with external professionals to support assessment and management of care. Further work is required to understand acceptability for residents and their families and effectiveness on family outcomes, particularly in non-Western cultures and low-middle income countries. Systematic review registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=254967, identifier: CRD42021254967.